Effectiveness of Citrus sinensis Aromatherapy and Nature Sound Therapy on Pain, Vital Signs, and Postoperative Nausea and Vomiting: A Quasi-Experimental Study - Ariningpraja, Rustiana Tasya; Fatma, Endah Panca Lydia; Lestari, Retno; Hidayati, Laely; Febriano, Luis Figo (Journal of Applied Nursing and Health, 2026)
Background: Postoperative recovery in the early hours after surgery is often accompanied by pain, vital-sign fluctuations, and postoperative nausea and vomiting (PONV). Complementary therapies such as Citrus sinensis aromatherapy and nature sound therapy have been used as adjuncts to pharmacological management; however, evidence on their combined effects on multiple recovery indicators in the early postoperative period remains limited. This study evaluated the effectiveness of these interventions compared with standard postoperative care. Methods: Three-group pretest–posttest quasi-experimental study was conducted in two hospitals using purposive sampling. Participants were conscious and hemodynamically stable adult patients 8–12 hours after surgery. Patients with chronic pain, hearing impairment, or olfactory dysfunction were excluded. Based on G*Power analysis (f = 0.25, α = 0.05, power = 0.80), 30 participants per group were required; therefore, 32 were recruited per group. Interventions were provided 8–12 hours post-surgery alongside standard care: Citrus sinensis aromatherapy (25 minutes) and nature sound therapy (30 minutes). Outcomes included pain intensity (Numeric Rating Scale), vital signs, and PONV severity (4-point scale). Data were analyzed using repeated-measures ANOVA in SPSS version 26. Results: Both Citrus sinensis aromatherapy and nature sound therapy showed significant improvements in pain, vital-sign stability, and reduced PONV severity compared with the control condition (p < 0.05). No adverse effects were observed. Aromatherapy demonstrated a moderate effect on PONV reduction, while nature sound therapy showed a large effect on pain reduction and vital-sign stabilization. Conclusion: Citrus sinensis aromatherapy and nature sound therapy are safe adjunctive interventions that may enhance early postoperative recovery by improving symptom burden and supporting physiological stability, with strong potential for integration into sensory-based postoperative comfort protocols.